FODMAPs, inflammatory bowel disease and gut microbiota: Updated overview on the current evidence - Simões, Catarina D. (2022)
Based on the fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) hypothesis, the low-FODMAP diet has been suggested as a potential therapeutic approach for infammatory bowel disease (IBD) with promising results on disease management. However, this diet implies a specifc broad food restriction, which potentially increases the risk of nutritional defciencies and may aggravate gut microbiota dysbiosis of IBD patients. The aim of the present study is to review the efect of individual FODMAPs on the human gut microbiota. In addition, this narrative review provides an updated overview of the use of the low-FODMAP diet in IBD, namely the implementation, advantages, limitations, and the impact on the gut microbiota